Zirconia implants and peek restorations for the replacement of upper molars - José María Parmigiani-Izquierdo; María Eugenia Cabaña-Muñoz; José Joaquín Merino; Arturo Sánchez-Pérez (SpringerOpen, 2017)
Abstract Background One of the disadvantages of the zirconia implants is the lack of elasticity, which is increased with the use of ceramic or zirconia crowns. The consequences that could result from this lack of elasticity have led to the search for new materials with improved mechanical properties. Case presentation A patient who is a 45-year-old woman, non-smoker and has no medical record of interest with a longitudinal fracture in the palatal root of molar tooth 1.7 and absence of tooth 1.6 was selected in order to receive a zirconia implant with a PEEK-based restoration and a composite coating. The following case report describes and analyses treatment with zirconia implants in molars following a flapless surgical technique. Zirconia implants are an alternative to titanium implants in patients with allergies or who are sensitive to metal alloys. However, one of the disadvantages that they have is their lack of elasticity, which increases with the use of ceramic or zirconia crowns. The consequences that can arise from this lack of elasticity have led to the search for new materials with better mechanical properties to cushion occlusal loads. PEEK-based restoration in implant prosthetics can compensate these occlusal forces, facilitating cushioning while chewing. Conclusion This procedure provides excellent elasticity and resembles natural tooth structure. This clinical case suggests that PEEK restorations can be used in zirconia implants in dentistry.